Implementasi Strategi Pembelajaran Berdiferensiasi dalam Meningkatkan Kemampuan Literasi dan Numerasi Siswa Sekolah Dasar pada pembelajaran Pendidikan Agama Islam di Kecamatan Leuwiliang Kabupaten Bogor - Mega Lestari; Chaira Saidah Yusrie; Yusi Srihartini (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
This study investigates the effectiveness of differentiated learning strategies in enhancing the literacy and numeracy skills of elementary school students in Islamic Religious Education (PAI) within Leuwiliang District, Bogor Regency. The research is motivated by the persistent issue of low literacy and numeracy skills among students in Indonesia, particularly in rural areas. This challenge is especially pronounced in PAI subjects, which require proficiency in reading Arabic texts and grasping religious concepts. Differentiated learning was selected as a viable solution, as it can tailor teaching methods to the individual needs and abilities of students. This research employs a qualitative method with a descriptive approach, collecting data through observations, in-depth interviews, and documentation involving teachers, students, and principals from several elementary schools in Leuwiliang District. The findings indicate that implementing differentiated learning strategies significantly enhances students' literacy and numeracy skills. Initially, only 30% of students demonstrated good literacy and numeracy abilities, but this figure rose to 60% in various school clusters following the implementation of these strategies. The study recommends further development of differentiated learning approaches, including training for teachers to improve their proficiency in applying this method. Additionally, integrating differentiated learning strategies into the PAI curriculum is crucial to ensure that learning remains adaptive and responsive to students' needs. In conclusion, differentiated learning strategies not only improve literacy and numeracy skills but also enrich the overall educational experience. This research aims to contribute to the advancement of more inclusive and quality education, particularly in elementary schools situated in rural areas.